2013
DOI: 10.1039/c2dt31983g
|View full text |Cite
|
Sign up to set email alerts
|

Computational Hammett analysis of redox based oxy-insertion by Pt(ii) complexes

Abstract: A computational Hammett analysis of oxy-insertion into platinum-aryl bonds is performed. Modeled transformations involve the two-step conversion of [((X)bpy)Pt(R)(OY)](+) (R = p- or m-X-C(6)H(4); Y = 4- or 3-X-pyridine; (X)bpy = 4,4'- or 5,5'-X-bpy; X = NO(2), H, OMe, NMe(2)) proceeding through a Pt-oxo intermediate to form aryloxide [((X)bpy)Pt(OR)(Y)](+), which contrasts a one-step non-redox (Baeyer-Villiger) oxy-insertion. A structural connection is proposed between redox and non-redox transition states, li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

1
5
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 28 publications
1
5
0
Order By: Relevance
“…1−16 With respect to the mechanism of the C−O bond formation, the oxygen atom of an oxidant (XO) is considered to be inserted into the M−C bonds in a concerted manner (Scheme 1a). 17,18 Cyclometalated complexes comprising group 8 elements and phpy have also been synthesized so far. 19−23 However, most of the research interests have been focused on effects of the strongly electron donating nature of the carbanion to the metal center on photochemical and electrochemical properties or cancer cell cytotoxicity, but little attention has been paid to the detailed reaction mechanism of the C−O bond formation.…”
supporting
confidence: 76%
See 4 more Smart Citations
“…1−16 With respect to the mechanism of the C−O bond formation, the oxygen atom of an oxidant (XO) is considered to be inserted into the M−C bonds in a concerted manner (Scheme 1a). 17,18 Cyclometalated complexes comprising group 8 elements and phpy have also been synthesized so far. 19−23 However, most of the research interests have been focused on effects of the strongly electron donating nature of the carbanion to the metal center on photochemical and electrochemical properties or cancer cell cytotoxicity, but little attention has been paid to the detailed reaction mechanism of the C−O bond formation.…”
supporting
confidence: 76%
“…It was confirmed that the oxygen atom of NMO (17 μmol) is not replaced with the labeled one by the reaction with H 2 18 O (100 μL, 5.0 mmol) in acetone (50 μL) at 25 °C for at least 5 h of reaction (Figure S6). If the oxido−osmium(V) species (Os V (O)(phpy)) is formed by the oxygen atom transfer from NMO to Os III (phpy), the oxido group can partially be replaced with the labeled oxygen atom of H 2 18O to form 18 Olabeled (Os V ( 18 O)(phpy)). If so, the labeled Os III ( 18 O-phpy) ([Os III Cl( 18 O-phpy)(tpy)] + ) will be produced from Os V ( 18 O)-(phpy).…”
mentioning
confidence: 99%
See 3 more Smart Citations